Analysis and research of the most common security threats for informational corporate network - Beliaiev, Ihor; Dovbush, Yuri (Видавництво Львівської політехніки, 2012)
An analysis of the most widespread vulnerabilities and attacks of corporate infomedia performed. The protection resources against network attacks and unauthorized access to network resources proposed and implemented.
Keywords: information security; network attack; DDoS; unauthorized access